TARI LIKOK PULO ACEH DI SANGGAR TARI RANGKANG ENDATU (KAJIAN TERHADAP KONSEP KOREOGRAFI) - LUCY OKTO PRITA (Gesture: Jurnal Seni Tari, 2014)
The theory used is the theory of dance, choreography theory of history and theory of this certainly will be closely linked with the object of such existing research on Likok Pulo Aceh dance in dance studio Rangkang Endatu. The population in this research is that there a few artists in dance studio Rangkang Endatu Taman Budaya located in Banda Aceh, Aceh Besar district. In conducting this research, the writer uses descriptive qualitative method and the locations in this study is in Rangkang Endatu dance studio located in Taman Budaya Aceh Banda Aceh Besar on the road Teuku Umar Taman Budaya Complex Setui Banda Aceh. Likok Pulo dance display concept that the original is in the dance studio Rangkang Endatu not much different, only there is a difference in the lyric and dance move Likok Pulo. Dance studio Rangkang Endatu make symbols of Islam as a theme in creating Likok Pulo dance in the dance studio. The concept of Likok Pulo dance existing dance studio Rangkang Endatu can be seen in terms of the composition of dance that has the concept of movements performed by dancers with unison, alternating, and sequential. Musical accompaniment in Likok Pulo dance in dance studio Rangkang Endatu useful as a regulator of the emotions of each of the dancers as well as play a role in regulating the tempo. The form of clothing on Likok Pulo dance same as the form of clothing in other Acehnese dance, which is a long shirt and trousers hand. Clothing Likok Pulo dance in dance studio Rangkang Endatu more creativity in colors and shapes that adorn the needlepoint cloth, by not eliminating the original concept in accordance with the teachings of Islam, which is recommended to cover the aurat. Keywords: Concept Choreography, Dance Likok Pulo